2004
DOI: 10.1016/j.micinf.2004.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis of influenza viruses

Abstract: Receptor-mediated endocytosis is known to play an important role in the entry of many viruses into host cells. However, the exact internalization mechanism has, until recently, remained poorly understood for many medically important viruses, including influenza. Developments in real-time imaging of single viruses as well as the use of dominant negative mutants to selectively block specific endocytic pathways, have improved our understanding of the influenza infection process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
274
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(284 citation statements)
references
References 59 publications
8
274
0
2
Order By: Relevance
“…10 Endocytosis may be further sub-categorized into either (a) phagocytosis, (b) pinocytosis, or (c) receptor mediated endocytosis, by either clathrin-mediated endocytosis or caveolinmediated endocytosis. 10,11 The particular endocytosis pathway utilized by the cell is dependent upon the surface chemistry, size, charge, and shape of the NP. 10 A current research drive has focused on increasing the cellular uptake of NPs and studies have shown that applying an external magnetic field enhances cellular uptake of mNPs, as well as the ability to target a diseased site.…”
Section: Introductionmentioning
confidence: 99%
“…10 Endocytosis may be further sub-categorized into either (a) phagocytosis, (b) pinocytosis, or (c) receptor mediated endocytosis, by either clathrin-mediated endocytosis or caveolinmediated endocytosis. 10,11 The particular endocytosis pathway utilized by the cell is dependent upon the surface chemistry, size, charge, and shape of the NP. 10 A current research drive has focused on increasing the cellular uptake of NPs and studies have shown that applying an external magnetic field enhances cellular uptake of mNPs, as well as the ability to target a diseased site.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by viral invasion of cells [1][2][3], significant efforts have been recently devoted to the design of synthetic nanoparticles (NPs) as drug carriers and/or imaging contrast agents [4][5][6][7]. The NPs are surface coated with ligands (e.g., antibody, peptide, and aptamer) that specifically target surface proteins (receptors) of cancer cells, thereby enhancing therapeutic efficacy and mitigating adverse side effects.…”
mentioning
confidence: 99%
“…Following fusion, influenza virus mainly enters the host cell via not only clathrin-dependent mechanisms, but also clathrin-independent and caveolin-independent mechanisms (Lakadamyali et al 2004), with the characteristics of macropinocytosis (de Vries et al 2011). Once internalized, these pathways are all equally efficient for virus fusion (Lakadamyali et al 2004).…”
Section: Avian Influenza Virusmentioning
confidence: 99%